Analysis of Good Corporate Governance Moderate The Relationship Between Corporate Social Responsibility, Profit Management, and Performance Profitability of Non-Cylical Consumer Sector Companies - Hirmansah, Ardi; Muda, Iskandar; Silalahi, Amlys Syahputra (Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of this research is to test and analyze the influence of corporate social responsibility, leverage, and profitability on company value, as well as testing and analyzing the role of good corporate governance in moderating the influence of corporate social responsibility, profit management, and profitability on company value. The data source used comes from the annual report. This research data was processed and analyzed using Warp PLS 7.0 software with the PLS-SEM analysis method. The research results show that the sample in this research is non-cyclical consumer sector companies. The researcher took the sample using a purposive sampling technique. Data testing uses path analysis. The research results show that the CSR variable has no effect on company value, the leverage and profitability variables have an effect on company value, the CSR variable through GCG has an effect on company value, the leverage and profitability variables through GCG have no effect on company value and earnings management has a significant and positive effect on value. Company Keywords: Corporate social responsibility; leverage; earnings management; profitability; good corporate governance; the value of the company